2011
DOI: 10.4315/0362-028x.jfp-10-547
|View full text |Cite
|
Sign up to set email alerts
|

Investigations on the Metabolism and Potentially Adverse Effects of Ethoxyquin Dimer, a Major Metabolite of the Synthetic Antioxidant Ethoxyquin in Salmon Muscle

Abstract: The feed additive ethoxyquin (EQ) is a commonly used synthetic antioxidant preservative in animal feeds. In farmed Atlantic salmon fillets, EQ residues are present, both as the parent compound and as EQ derivatives. One of the main EQ derivates in fish muscle is an ethoxyquin dimer (EQDM), and the potential toxicity of this metabolite is not known. The aim of this study was to evaluate the metabolism and potentially toxicological effects of EQDM. A 90-day subchronic exposure study with repeated dietary exposur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…The occurrence of such residues and their transfer to edible tissues of salmon may therefore be a new phenomenon, constituting a novel route of exposure (or increased exposure) to consumers Feed production Growing Lack of residue and safety data on certain metabolites of contaminants (e.g. newly discovered metabolites of ethoxyquin, leuco dyes, pesticides, etcetera, or residues not commonly included in residue monitoring) (Ørnsrud et al, 2011;Chan et al, 2012)…”
Section: Chemical Hazardsmentioning
confidence: 99%
See 2 more Smart Citations
“…The occurrence of such residues and their transfer to edible tissues of salmon may therefore be a new phenomenon, constituting a novel route of exposure (or increased exposure) to consumers Feed production Growing Lack of residue and safety data on certain metabolites of contaminants (e.g. newly discovered metabolites of ethoxyquin, leuco dyes, pesticides, etcetera, or residues not commonly included in residue monitoring) (Ørnsrud et al, 2011;Chan et al, 2012)…”
Section: Chemical Hazardsmentioning
confidence: 99%
“…Until 2009, it was also authorised in the EU as pesticide (2015b). In the fish, ethoxyquin is converted to an ethoxyquin dimer, which has been detected in liver and muscle from Atlantic Salmon (Ørnsrud et al, 2011;EFSA, 2015b). Although ethoxyquin is commonly used as feed additive, it is not authorized as a food additive in the EU (Ornsrud et al, 2011).…”
Section: Feed Additives and Processing Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…They are also known to display a wide range of biological and pharmaceutical properties including antioxidant [16,17], anti-inflammatory [18] and hormone receptor modulating [19] properties. Furthermore, ethoxyquin (6-ethoxy-1,2-dihydro-2,2,4-trimethylquinoline) is a powerful antioxidant approved by the Food and Drug Administration (FDA) and authorized in the European Union for use as additives in animal foods [17,20]. However, despite its potent radical scavenger activity, the significant hypothermic effect of ethoxyquin in rodents [21] has precluded its potential use for central nervous system protection in human [22].…”
Section: Introductionmentioning
confidence: 98%
“…However, the use of ethoxyquin as a food additive for human consumption is prohibited. Although the effects of the presence of this ethoxyquin dimer in human through a carryover from edible fish parts have not been studied [7,11,12], this compound was shown to be associated with the modulation of hepatic detoxifying enzymes [13] and the alteration in gene and protein expression patterns in fish [11,12] and in male F344 rats [7]. In fact, the study of the muscles of Atlantic salmons fed with ethoxyquin-preserved feedstock has indicated that 6-ethoxy-1-(6-ethoxy-1,2-dihydro-2,2,4-trimethylquinolin-8-yl)-1,2-dihydro-2,2,4-trimethylquinoline, one of the C,N-linked ethoxyquin dimers described in this report, was the main and ubiquitous metabolite of dietary ethoxyquin in fish [2,6,11,12].…”
Section: Introductionmentioning
confidence: 99%